IMPROVEMENT OF CIVIL LEGAL REGULATION OF CONTRACTUAL RELATIONS ON MEDICAL SERVICES - Abdullaev Jamshid Djamilovich (American Journals Publishing, 2024)
The article analyzes the issues of improving the civil legal regulation of some contractual relations in the provision of medical services (liver transplantation, heart stenting, transplantation of human organs and tissues, artificial insemination, kidney transplantation). Also, the issues of sustainable development of medical service contracts in the daily medical contractual practice of developed countries, improvement of civil legal features in terms of contract law, and information on the experience and theoretical knowledge of the world countries in this matter are covered.
Keywords: Transplantation of human organs and tissues, HRSA, WHO